Swastika symbol on the Pillar capital - Temples of India Project Team (Jio Institute, 2024)
The pillar capital in the picture has a Swastika symbol, one of the eight auspicious symbols of Jainism. It is surrounded by floral motif bands. The band flanking the Capital has a depiction of scenes from the city of Bikaner where people are seen going to the market, travelling on elephant back, shops in marketplaces, etc.